Delayed Postoperative Neurologic Deficits in Spinal Deformity Surgery. Issue 3 (February 2016) - Auerbach, Joshua D.; Kean, Kristin; Milby, Andrew H.; Paonessa, Kenneth J.; Dormans, John P.; Newton, Peter O.; Song, Kit M.; Lonner, Baron S.
Abstract : Supplemental Digital Content is available in the text Abstract : Study Design: A cross-sectional survey of surgeon members of the Scoliosis Research Society (SRS). Objective: This study sought to characterize the incidence, clinical presentation, diagnostic workup, treatment, and neurologic prognosis following delayed postoperative neurologic deficit (DPND) in patients undergoing spinal deformity surgery. Summary of Background Data: DPND is a potentially devastating condition following spinal surgery, characterized by the development of a neurological deficit within hours or days of the surgical procedure. To date, only case reports and small case series have been published on the topic. Methods: We developed a survey to characterize DPND following spinal deformity surgery. This survey was distributed to surgeon members of the SRS through email and standard mail. The overall response rate was 38% (352/929). Results: Our results suggest an estimated DPND incidence of 1 of 9910 cases (0.01%). Eighty-one surgeons (23%) experienced at least 1 DPND in the past 10 years (92 total cases). Most common diagnoses were scoliosis (69%), kyphosis (23%), and spondylolisthesis (14%); 20% were revision surgeries. The number of hours to deficit onset was as follows: 1 to 12 (36%), 13 to 24 (27%), 25 to 48 (27%), more than 48 (10%). The most commonly cited sources of injury included ischemic injury (38%) and cord compression (15%). Forty-one percent experienced complete neurologic recovery, 26% partial, and 33% no recovery. Twenty-one percent of patients achieved final neurologic status within 1 week, 38% by 1 month, and 73% by 6 months. Patients with compression-related DPND had a significantly greater likelihood of experiencing some neurologic recovery (≥1 ASIA Grade) than ischemia-related DPND (86% versus 51%, P = 0.049). Conclusions: DPND occurs at an estimated incidence of 0.01%. Sixty-three percent of DPND cases occurred within the first 24 hours and 90% within 48 hours. Complete (41%) or partial (26%) neurologic recovery may be expected, especially in compression-related DPND, emphasizing the need for perioperative vigilance, prompt recognition, and early intervention. Level of Evidence: 4